The positive economics of corporatism and corporate governance - Rainer Fehn; Carsten-Patrick Meier (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, Wirtschaftsordnung und Sozialpolitik, 2000)
This paper presents a positive model which shows that institutional setups on capital and labor markets might be intertwined by politicoeconomic forces. Two politicoeconomic equilibria arise from our model, one with little protection of insiders on capital and labor markets, and another one with an institutional bias toward favoring insiders on both markets. Coherent and relatively homogeneous societies, where binding commitments enjoy greater feasability, are more likely to be found in the latter, corporatist equilibrium, whereas fragmented, heterogeneous Anglo-Saxon societies fit better into the former category. These predictions of the model receive considerable support in our crosscountry empirical analysis, thus being potentially important for the current debates concerning the reforms of labor markets and of corporate governance systems.
Keywords: 330